TOPSIS Method on Selection of New Employees' Acceptance - Diena Rauda, Ramdania; Manaf, Khaerul; Fikri, Rahmat Junaedi; Fathonih, Ah.; Ana, Hadiana (2020)
A hospital is a labor-intensive organization that requires many personnel and professions from various disciplines. Employees are one of the determinants of the success of a company. One way that agencies use to obtain qualified employees is by making a selection at the time of employee recruitment. The problem that is often encountered is that parttime employee selection is calculated objectively so that it is less efficient and accurate in the selection process. Decision support systems with the TOPSIS method are considered suitable to assist the personnel section of the public Hospital in selecting prospective part-time employees. TOPSIS is a multicriteria decision-making method based on a concept where the chosen alternative has the closest distance from a positive ideal solution and also has the farthest distance from a negative ideal solution. The completion criteria applied to the selection of employees include the results of written tests, psychological tests, health tests, and interviews. The results of the tests show that the TOPSIS method can be used well in selecting and sorting from the largest to the smallest value with an accuracy rate of 85% in the amount of 20 data.